Kritik Restorative Justice dalam Kasus Pelecehan Seksual di Pesantren: Analisis Undang-Undang No. 12 Tahun 2022 - Sari Ritonga, Indah Maya; Sastra Panjaitan, Budi (IAIN Langsa, 2024)
This study discusses the implementation of Restorative Justice in a case of sexual harassment at a pesantren in Langkat, highlighting the discrepancy between the ideal concept of justice and the practice that should align with Law No. 12 of 2022 concerning Sexual Violence Crimes. The study aims to analyze the application of Restorative Justice in this specific case of sexual harassment at the pesantren and to evaluate its compliance with the applicable legal provisions, particularly Law No. 12 of 2022. The research methodology employs a normative juridical approach, involving the analysis of legal documents and a case study on the implementation of Restorative Justice at a pesantren in Langkat. The findings show that the implementation of Restorative Justice in this case is not consistent with the provisions of Law No. 12 of 2022, particularly in terms of victim protection. The peaceful agreement reached tends to overlook the rights of the victim and fails to provide an adequate deterrent effect on the perpetrator. This indicates that the application of Restorative Justice invites considerable criticism and needs to be re-evaluated, especially in the context of sexual violence cases classified as serious crimes.